HUBUNGAN TINGKAT PENGETAHUAN TERHADAP KEJADIAN KEPUTIHAN FISIOLOGIS DAN PATOLOGIS PADA REMAJA - Annisa, Annisa; Salsabila Nurvinin; Muhammad Yusuf Arrozhi; Adnan Abdullah; Khairina Hashifah (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2024)
One of the reproductive health problems in adolescents is vaginal discharge (fluor albus). According to WHO, around 75% of women in the world have experienced vaginal discharge once in their lives. The high incidence of vaginal discharge is thought to be related to a lack of sufficient information about reproductive health. The study aims to determine the relationship between the level of vaginal hygiene knowledge and vaginal discharge in adolescents. This is a cross sectional study to determine the relationship between the level of vaginal hygiene knowledge and vaginal discharge in adolescents. Primary data obtained by questionnaire for 202 samples. Univariate analysis and chi-square test are used. Acording to the univariate analysis, the level of knowledge of vaginal hygiene in young women at Junior High School 1 Jatirogo was mostly in the moderate category, 198 respondents (98%), and the incidence of vaginal discharge in adolescents was mostly in the normal (physiological) category, 178 respondents (88.1%). Of the 202 respondents who had sufficient knowledge and normal vaginal discharge, there were 176 respondents (87.1%), this was evidenced by the chi-square test which showed a p value > α = 0.017. Here we conclude there is a relationship between the level of knowledge of vaginal hygiene and vaginal discharge in adolescents.